Analysis Of Economic Opportunities For Farming With Hydroponic Systems In Makassar City - Asdar; Arniati; Fiqrizal; Nur Hikmah; Alda Susanti (Jurnal Manajemen Bisnis, 2023)
This research delves into the world of hydroponic farming within the vibrant landscape of Makassar City, aiming to uncover the city's untapped economic potential. We meticulously selected a group of dedicated garden owners and experienced hydroponic growers from the city using a systematic snowball sampling strategy to provide insights into this topic. Our analytical framework is built on the SWOT analysis, a strategic tool rooted in logical principles. It harnesses strengths and seizes opportunities while mitigating weaknesses and averting potential threats. As we explore the four key aspects of strengths, weaknesses, opportunities, and threats, an intriguing narrative unfolds, showcasing Makassar City's robust business environment and extensive economic opportunities poised for greater growth and prosperity. These findings are bolstered by a well-executed marketing strategy utilizing various media platforms. Summarizing our observations on the Cartesian diagram, our SWOT analysis confidently resides in the first quadrant, indicating an overwhelmingly positive outlook for hydroponic farming in the city.